Exploring the Challenges of Developing Speaking Skills in Mechanical Engineering ESP Students: Insights from State Polytechnic of Subang - Nurizzi Rifqi Ferdian; Rian Dwi Aji Saputro (Jurnal Impresi Indonesia, 2026)
The increasing demands of the global industrial sector require Mechanical Engineering graduates to possess specialized oral English proficiency, positioning English for Specific Purposes (ESP) as a critical component of vocational higher education. This research aimed to analyze the professional communicative needs, skill deficiencies, and instructional preferences related to speaking skills among students within the Indonesian polytechnic context. A convergent parallel mixed-methods design was employed at State Polytechnic of Subang, involving a validated Likert-scale questionnaire administered to 100 first-semester students and semi-structured interviews with a purposive subsample of 15 participants. The findings highlighted a high perceived necessity for technical oral genres, particularly technical presentations and the description of mechanical blueprints. Despite this necessity, students reported significant deficiencies in fluency and technical vocabulary. These linguistic challenges were further complicated by affective barriers, such as speaking anxiety, and cognitive struggles regarding memory retrieval and idea formulation under pressure. Consequently, students expressed a strong preference for instructional methods centered on authentic simulations, Task-Based Learning (TBL), and the Genre-Based Approach (GBA). This study concludes that bridging the speaking proficiency gap necessitates a shift toward highly contextualized, practice-based methodologies that integrate affective support strategies to reduce learner anxiety. Implementing such a framework is essential for equipping vocational engineering graduates with the specialized communicative competence required to succeed in high-stakes professional environments.